BEST PRACTICES FOR PRIVACY-PRESERVING AI IN SALESFORCE ENVIRONMENTS - Sruthi Potru, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive technical article presents an in-depth framework for implementing ethical AI and data privacy measures within Salesforce environments, addressing the critical challenges faced by organizations in balancing innovation with responsibility. This article examines fundamental aspects of ethical AI deployment, including bias prevention methodologies, privacy-preserving machine learning techniques, and regulatory compliance mechanisms across global privacy standards. Through detailed analysis, it explores the implementation of robust technical measures, including advanced data masking, encryption protocols, and role-based access control systems, alongside comprehensive guidelines for continuous AI model auditing and bias detection. The article provides practical insights into establishing effective monitoring systems and incident response procedures, emphasizing the importance of maintaining transparent operations while protecting sensitive data. Special attention is given to privacy-by-design principles and their integration throughout the AI development lifecycle, offering organizations a structured approach to building trust with stakeholders while maintaining compliance with evolving regulatory requirements. By examining real-world implementations and industry best practices, this article presents actionable strategies for organizations seeking to leverage AI capabilities within their Salesforce environments while upholding the highest standards of ethics and privacy protection. The findings highlight the importance of establishing comprehensive governance frameworks, maintaining continuous adaptation to emerging challenges, and fostering a culture of responsible AI development. This article contributes to the growing body of knowledge on ethical AI implementation, providing valuable insights for practitioners, developers, and decision-makers in the field of AI-powered CRM systems.